Religious-Based Maritime Education for the Introduction of Bugis- Makassar Marine Traditions and Culture at SD 82 Pattene Maros - Rifal; Dyan Paramitha Darmayanti; Ahmadin; Muh. Rasyid Ridha; Hasni (Edumedia Solution, 2025)
This community engagement program titled “Religious-Based Maritime Education for Introducing Bugis-Makassar Sea Traditions and Culture at SD 82 Pattene Maros” was conducted in response to the declining awareness of local maritime traditions among young students due to modernization and limited exposure to cultural and religious values in formal education. The community partners—teachers and students in a coastal primary school—faced challenges in integrating local maritime knowledge and spiritual values into daily learning. To address this, the team designed a participatory-educative approach by developing a thematic module combining Islamic moral teachings with Bugis-Makassar maritime traditions such as sailing, fishing, and coastal rituals. The implementation took place one week before the Haul Akbar of Tarekat Khalwatiyah Samman, a local religious event, to strengthen students’ understanding of spirituality, community solidarity, and cultural heritage. Activities included classroom learning, storytelling, field observation at coastal areas, and reflection sessions guided by teachers and community leaders. The results showed significant improvements in students’ enthusiasm, religious character, social cooperation, and ecological awareness. They demonstrated greater respect for local culture, care for the marine environment, and appreciation of their Bugis-Makassar identity. This program concludes that integrating religious and maritime education effectively preserves local wisdom while fostering moral and cultural character formation among coastal students in Indonesia.